Photo-catalytic degradation of Acid Yellow 17 azo dye using ZrO2-CeO2 hollow microspheres as a catalyst - Farooq, M. (Desalination Publications, 2019)
In the present study, ZrO2-CeO2 hollow spheres have been synthesized using carbon spheres as a template. The physico-chemical, textural and morphological properties of the synthesized ZrO2-CeO2 hollow spheres were explored by powder X-ray diffraction, N2-physisorption, Fourier emission scanning electron microscopy (FESEM) and X-ray photoelectron spectroscopy techniques. The catalytic activity of the synthesized ZrO2-CeO2 catalyst was evaluated in the degradation of acid yellow 17 dye using advanced oxidation technique. The results demonstrated that the ZrO2-CeO2 hollow spheres showed the highest percentage degradation of 88 in reaction time of 180 min for the selected dye. The improved degradation activity of the synthesized catalyst could be attributed to the fact that the oxidizing agent H2 O2 react with ZrO2-CeO2 to produce highly reactive hydroxyl radical (âOH) which further attack on the selected dye molecule and degraded to less environmental toxic components. Â© 2019 Desalination Publications. All rights reserved.